THE HISTORICAL NARRATION OF RAMLAH BATTLE (573 AH/ 1174CE) , THROUGH THE PERSPECTIVE AND VISION OF THE FAMOUS HISTORIAN IMADADDIN AL-ASFAHA - Ahmed, Karvan Mohammed; Ali, Sipan Hassan (Journal of Duhok University, 2018)
The research aims to stand objectively on the historical narration of Ramlah Battle (573 AH/ 1174CE) , through the perspective and vision of the famous historian Imadaddin Al-Asfahani and introducing the preparations mad by Sultan Salahuddin to carry out the campaign and the procedures he took to enter the lands of the Crusaders in the Levant. Then, the strategy he adopted during his presence with the Ayyubid Army in the Crusaders areas and finally, the factors that caused the defeat of Sultan Salahuddin in the battle. The Battle of Ramlah is one of the most famous military battles in the history of the Ayyubid State during the reign of the Crusades. It was the first official defeat of the rule of Salahuddin by the Crusaders directly in a military clash. This defeat changed the strategic and military thinking of the Sultan towards more sophisticated pursuits. In accordance with the vision of one of the contemporary historians who accompanied the Sultan during the initial stages of preparation for that campaign, namely (Imadadin Al-Asfahani) as the researcher mentions that no special study had been done regarding the battle. Therefore, (The Battle of Ramlah in the narration of Imadadin Al - Asfahani through his book Al - Barak Al - Shami (597 AH / 1201 AD) - An Analytical Study) is chosen to be the topic of this research. The research is divided into two main parts as well as the introduction and the conclusion. The introduction is devoted to discuss the biography of the historian Imadadin Al- Asfahani, his social life and his relation with the Zankid and the Ayyubid states. Concerning the first part, it discusses the preparations of Sultan Salahuddin Al-Ayyubi for the Rmlah Battle and the procedures to prepare for the campaign. As for the second part, it focuses on the Sultan Sallahuddin’s path, his attack on Ashkelon, and eventually, the main outcomes of the Ramlah Battle.